A Helical tomotherapy as a robust low‐dose treatment alternative for total skin irradiation. Issue 5 (29th April 2019) - Haraldsson, André; Engleson, Jens; Bäck, Sven Å. J.; Engelholm, Silke; Engström, Per E.
Abstract: Mycosis fungoides is a disease with manifestation of the skin that has traditionally been treated with electron therapy. In this paper, we present a method of treating the entire skin with megavoltage photons using helical tomotherapy (HT), verified through a phantom study and clinical dosimetric data from our first two treated patients. A whole body phantom was fitted with a wetsuit as bolus, and scanned with computer tomography. We accounted for variations in daily setup using virtual bolus in the treatment plan optimization. Positioning robustness was tested by moving the phantom, and recalculating the dose at different positions. Patient treatments were verified with in vivo film dosimetry and dose reconstruction from daily imaging. Reconstruction of the actual delivered dose to the patients showed similar target dose as the robustness test of the phantom shifted 10 mm in all directions, indicating an appropriate approximation of the anticipated setup variation. In vivo film measurements agreed well with the calculated dose confirming the choice of both virtual and physical bolus parameters. Despite the complexity of the treatment, HT was shown to be a robust and feasible technique for total skin irradiation. We believe that this technique can provide a viable option for Tomotherapy centers without electron beam capability.